The Influencing Factors of Customer Experience And Its Effect On Brand Equity In Seto Hasbadi Hospital Bekasi - Suprapto, Yogi Mandala (Jurnal Manajemen, 2023)
As consumers of health services, patients are increasingly aware of their rights and demand quality health services. The high quality of hospital services is expected to lead to satisfaction and positive patient experiences, which can positively affect the hospital's brand. Brand equity is a precious hospital asset to face a competition between hospitals. Seto Hasbadi Hospital faces stiff competition in Bekasi City with 40 other hospitals. In this study, Seto Hasbadi Hospital wanted to find out how the marketing activities affect the customer experience, which affects the Customer-Based Brand Equity (CBBE). This research uses marketing variables: physical environment, interpersonal care activity, technical process, administrative process, core services, service communication, access convenience, social responsibility, customer experience, and customer-based brand equity (CBBE). The number of samples in this study was 376 respondents with data analysis using Structural Equation Modeling with SmartPLS software. Marketing activities that positively and significantly impact customer experience are the physical environment, access, convenience, and social responsibility. The customer experience variable positively and significantly affects the Customer-Based Brand Equity variable. Because the R square value of the Customer-Based Brand Equity is very small, further research can look for other factors that can affect the brand equity of Seeto Hasbadi Hospital